Population Trends of the Maleo (Macrocephalon maleo SCLATER, 1860) and Conservation Efforts - Maleke, Claimen M.; Pollo, Hard Napoleon (Asia Pacific Journal of Interdisciplinary Studies, 2026)
The Maleo (Macrocephalon maleo) is an endemic species of Sulawesi facing serious threats of extinction due to habitat loss, poaching, and disturbance at nesting sites. This article presents a comprehensive review of Maleo population dynamics over the past decade (2013–2024), analyzes the effectiveness of implemented conservation strategies, and identifies research gaps requiring further attention. The study synthesizes peer-reviewed literature, field monitoring reports, and official data from conservation agencies. Results indicate that Maleo populations have declined at an average rate of 3–5% annually, with habitat loss accelerated by agricultural expansion and settlement growth. Current estimates suggest only 4,000–8,000 mature individuals remain in the wild, classifying the species as Endangered (EN) on the IUCN Red List. Community-based conservation programs and semi-in situ management in parts of Central and North Sulawesi have shown promising results, with hatching success rates of 60–80% at managed sites. However, fragmented cross-regional policies and limited long-term funding remain unresolved structural barriers. An integrated conservation approach combining ecological, social, and governance dimensions is essential to ensure the species’ long-term survival.